Propagation of nominal shocks in open economies - Torben M. Andersen; Niels C. Beier (Danmarks Nationalbank, 2002)
Empirical evidence documents substantial persistence in the adjustment process to nominal shocks. Existing open-economy models have failed either to generate interesting dynamics or found that the mechanisms are quantitatively weak. We consider the propagation of nominal shocks in a fully specified stochastic intertemporal open-economy model with incomplete capital markets and staggered nominal wage contracts. It is shown that persistence depends on wage-price interdependencies (spiral), which in turn in a general-equilibrium setting depends on structural parameters characterizing both the demand and the supply side of markets. Parameter choices strengthening wage-price interdependencies thus strengthen persistence as is demonstrated analytically and illustrated numerically. A further product of the paper is that it develops a method by which to solve explicitly for a stochastic intertemporal version of the New Open-Economy Macroeconomics model in which the expenditure switching effect is effective.
Keywords: E32; F41; 330; current account; exchange rates; incomplete capital markets; nominal shocks; persistence; staggering; Schock; Offene Volkswirtschaft; Leistungsbilanz; Zwei-Länder-Modell; Theorie